2019
DOI: 10.1007/s11906-019-0943-x
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the 2017 AAP Clinical Practice Guidelines for Management of Hypertension in Children and Adolescents: a Review

Abstract: Purpose of Review-To evaluate the impact of the 2017 American Academy of Pediatrics Clinical Practice Guideline (2017 AAP CPG) for Screening and Management of High Blood Pressure in Children and Adolescents. Recent Findings-The 2017 AAP CPG had several significant changes compared to the 2004 Fourth Report. This review will focus on the emerging evidence from the first studies to apply the 2017 AAP CPG and the simplified table it contains on the overall prevalence of HTN and on recognition among children and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…In recent years, the publication of the AAP guidelines has generated a heated debate on which are the most appropriate criteria for the screening and diagnosis of HTN in children and adolescents. 20,21 As a result of the lowered blood pressure (BP) cut-offs, the new guidelines are undoubtedly expected to increase the number of young people at risk of HTN as compared with the criteria of the Fourth Report 5–7 or the ESH. 13 However, on the basis of the results provided by the present study, the use of the AAP reference values allows the identification of young people with a greater burden of CVR who would have been missed using the ESH criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the publication of the AAP guidelines has generated a heated debate on which are the most appropriate criteria for the screening and diagnosis of HTN in children and adolescents. 20,21 As a result of the lowered blood pressure (BP) cut-offs, the new guidelines are undoubtedly expected to increase the number of young people at risk of HTN as compared with the criteria of the Fourth Report 5–7 or the ESH. 13 However, on the basis of the results provided by the present study, the use of the AAP reference values allows the identification of young people with a greater burden of CVR who would have been missed using the ESH criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the American Academy of Pediatrics has updated its recommendations on recognition of HBP in children and adolescents by including new simplified screening tables with BP cut‐offs at the 5th percentile for height for every child under the age of 13 years 5 . However, this approach gives the table more than 99% sensitivity to detect HBP values that may result in an overall increase in prevalence of HBP, particularly in overweight and obese children who are at higher risk of CVD 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…A number of guidelines are available to define hypertension, each resulting in a different prevalence of hypertension [ 38 , 51 ]. We decided to define prehypertension and hypertension based on the 90th and 95th percentile of the guidelines from the AAP 2017, respectively [ 52 ]. Recent literature has shown that the AAP 2017 guidelines result in a higher prevalence of hypertension compared to two other frequently used guidelines [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has shown that the AAP 2017 guidelines result in a higher prevalence of hypertension compared to two other frequently used guidelines [ 53 , 54 ]. Nevertheless, the AAP 2017 guidelines are expected to better recognize youth that are at high risk for cardiovascular disease, and have been therefore recommended in the recent literature [ 52 , 55 ]. In addition, the Dutch children in our study were relatively tall compared to the reference population of the AAP 2017 guidelines, and even though the hypertension cut-offs are height-dependent, the tallness of our study population may have resulted in an overestimation of hypertension.…”
Section: Discussionmentioning
confidence: 99%